2016
DOI: 10.1186/s10194-016-0615-z
|View full text |Cite
|
Sign up to set email alerts
|

Field testing primary stabbing headache criteria according to the 3rd beta edition of International Classification of Headache Disorders: a clinic-based study

Abstract: BackgroundThe diagnostic criteria for primary stabbing headache (PSH) in the 3rd beta edition of International Classification of Headache Disorders (ICDH-3 beta) were recently revised. In the ICDH-3 beta, PSH is defined as short-lasting head pain spontaneous occurring as a single stab or series of stabs without autonomic symptoms and involving all head areas (i.e., not limited to the ophthalmic branch region of the trigeminal nerve). The aim of this study was to investigate the validity of the ICHD-3 beta crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
0
14
3
Order By: Relevance
“…Previous studies have reported different demographics and characteristics [ 4 , 7 , 12 , 17 , 18 ]. Our results showed that different characteristics were involved in the chronicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported different demographics and characteristics [ 4 , 7 , 12 , 17 , 18 ]. Our results showed that different characteristics were involved in the chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria for PSH have recently been revised in the ICHD 3rd edition beta version (ICHD-3 beta), particularly regarding the location of the pain and associated symptoms [ 3 ]. Most PSH patients have very brief attacks [ 4 7 ]. Migraineurs often have PSH, during or independently from migraine attack [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study 27 enrolling 280 individuals with headache with a stabbing quality of pain, 245 of them were followed up for 2 weeks. Secondary causes for SH were observed in nine patients (3.7%, herpes zoster in seven patients and Bell's palsy in two patients).…”
Section: Discussionmentioning
confidence: 99%
“…We also had the chance to examine patients complaining of SH In a study 27 enrolling 280 individuals with headache with a stabbing quality of pain, 245 of them were followed up for 2 weeks.…”
Section: Re Sultsmentioning
confidence: 99%
“…Bodily jabs have been reported infrequently in population-based surveys (1.1% in the Vågå study) (24); however, they are relatively common in clinical studies (12–13%) (5,17). Allodynia has been reported in 19–37% of patients in clinic-based studies (5,16,17). While nausea, vomiting, photophobia, and phonophobia have been reported as accompanying symptoms (5,14), they are not prominent in most patients with typical PSH that does not overlap with migraine attacks.…”
Section: Clinical Manifestationmentioning
confidence: 99%